Pengaruh Model Pembelajaran Kooperatif Learning Tipe Jigsaw Dan Minat Belajar Siswa Terhadap Hasil Belajar Siswa Kelas Vii Pada Mata Pelajaran Ilmu Pengetahuan Sosial Terpadu Di Mtsn 6 Padang - Nada - Uljannah; Stevani Stevani; Rika Verawati (STKIP PGRI Sumatera Barat, 2022)
This study aims to analyze: 1) the learning outcomes of Integrated Social Studies students who are taught using the Jigsaw Type Cooperative Learning Model are higher than students who are taught using the conventional model at MTsN 6 Padang. 2) The effect of learning outcomes on interest in learning in Integrated Social Studies subjects for class VII students at MTsN 6 Padang. 3) The interaction between the Jigsaw Type Cooperative Learning Model and the conventional learning model with students' interest in learning about student learning outcomes in Integrated Social Studies subjects at MTsN 6 Padang.This type of research is quantitative. This research was conducted at MTsN 6 Padang with a population of 431 and a sample of 62 students consisting of 30 control classes and 32 experimental classes. Instruments in this study through the distribution of questionnaires and tests. The data analysis techniques used are validity test, reliability test, level of difficulty, discriminatory power, normality test, homogeneity test and two-way ANOVA test.The results showed that (1) Students who were taught using the Jigsaw Type Cooperative Learning Model had significantly higher learning outcomes when compared to students who were taught through conventional methods with Sig. = 0.029 < = 0.05, thus H0 was accepted. Ha rejected, which means the Jigsaw Type Cooperative Learning Model can be used in the learning process. (2) students who have a significant interest in learning have higher learning outcomes when compared to students who have a low interest in learning with Sig. = 0.000 < = 0.05, thus H0 is accepted. Ha is rejected, where students have high interest. have high learning outcomes, students who have low interest have low results. (3) There is no effect of the application of the jigsaw type of cooperative learning model with learning interest on the learning outcomes of class VII MTsN 6 Padang students, this can be seen from the results of the two-way ANOVA test with a value of sig.0.512>α i.e. 0.05 so H0 is rejected Ha accepted.Keywords: Jigsaw Type Cooperative Learning, Interest in Learning, Learning Outcomes